EFEKTIFITAS SUPLEMENTASI ZINK DALAM PENCEGAHAN MALNUTRISI (STUNTING DAN WASTING) PADA ANAK BALITA - Sulistyowati, Dwi Ariani (Bajang Institute, 2024)
Background: The prevalence of stunting in Indonesia is still high. WHO said in 2018 the prevalence of stunting was 30.80%, an increase compared to 29.6% in 2017 (WHO, 2018). Every year about 10.5 million child deaths are attributed to malnutrition and > 90% occur in developing countries. One of the 2nd goals of the Sustainable Development Goals (SDGs) is to end all forms of malnutrition in children under five by 2030, and also achieve the international target of reducing stunting and wasting by 2025 (WHO, 2016). Stunting is a chronic nutritional disorder with a multifactor etiology. One of them is low levels of zinc in the blood which causes low immunity and subsequently slowed growth. According to the International Zinc Nutrition Consultative Group (IZNCG) the global prevalence of zinc deficiency is around 31% with the highest prevalence areas in South Africa, Central 37-62% then North and East Africa 25-52% and South Asia and Southeast Asia. Based on the results of the Indonesian Nutritional Status Survey (SSGI) conducted by BKKN that in Indonesia toddlers with a zinc deficit of 21.6%, the stunting prevalence rate starting in 2018 has decreased better but the incidence of stunting in toddlers is still a public health problem in Indonesia. Objective: This study aims to determine the effect of Zinc Supplementation on the increase in body weight, TB, the incidence of upper respiratory tract infections and the incidence of diarrhea in toddlers. Method: This type of research is Quasi-experimental with pre-post test one group design. The independent research variables are zinc syrup and the dependent variables are an increase in body weight, TB, the incidence of upper respiratory tract infections and the incidence of diarrhea in toddlers. Results: The results of the Paired Samples T-test showed changes in body weight before and after zinc administration with a result of 0.004 which means zinc supplements are effective in increasing weight for toddlers. The average showed an increase in body weight before and after zinc administration of 421 grams p value 0.001 and the average TB increased by 0.866 cm with a value of p = 0.662. Conclusion: There is an effect of zinc supplementation on the increase in body weight, increase in TB, incidence of upper respiratory tract infections and incidence of diarrhea in toddlers